Analisis Strategi Pemasaran dalam Meningkatkan Omset Penjualan Produk Tanaman Hias Ditinjau dari Perpektif Ekonomi Islam - Sulton Baihaqi Ahmad; Abdur Rohman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The current situation has forced MSME players to think about ways to get up after the pandemic, because previously the impact of the pandemic had greatly affected the businesses they were running. This research is aimed at exploring the marketing strategies used by Cv Crips Store Farm to increase sales turnover due to the impact of the pandemic. using descriptive qualitative research, with a field study approach, namely an approach that uses information obtained from research targets who go directly to the research site. By using primary data obtained directly through the results of interviews with informants. The results showed that 80% of all sales were focused on through the marketplace, by implementing the marketing mix strategy, by implementing the 5P strategy, namely strategy is planning, strategy is pattern, strategy is position, strategy is play, and strategy is perspective. While the implementation of the current strategy, its implementation is in accordance with Islamic legal review, by prioritizing 4 (four) characteristics of shari'ah marketing, namely divinity (rabbaniyyah), ethical (akhlaqiyyah), realistic (al-waqi'iyyah) and humanistic ( insaniyyah). The result of implementing the company's marketing strategy is an increase in the percentage of sales by 80% compared to before implementing the marketing strategy.